Pengaruh Infra Red Terhadap Penurunan Skala Nyeri Pada Pasien Low Back Pain Myogenic Di Rumah Sakit Khusus Bedah Hasta Husada Kepanjen Malang - Vivi Endaryanti; Wiek Israwan; Amin Zakaria; Fransisca Xaveria Hargiani (Jurnal Keperawatan Muhammadiyah, 2022)
Objective: Low Back Pain Myogenic is a problem that occurs due to stress on the muscles around the lower back. Giving physiotherapy modalities is one of the treatments for myogenic low back pain. Physiotherapy modalities that can be used in cases of low back pain are infra red.Methods: The method used in this study is a pre-experimental design, which uses one group pre and posttest where the research subject is taken only one group. The research was carried out from September to October 2021 with 8 treatments using infra red with Visual Analoq Scale (VAS) measurements, data collection techniques according to inclusion and exclusion criteria with a sample of 30 respondents.Results: From the results of research conducted on 30 respondents with an age range of 25 to 65 years at the Medical Rehabilitation Installation of the Hasta Husada Surgical Hospital in Kepanjen, Malang by giving Infra Red to Low Back Pain Myogenic patients, changes in the Visual Analoq Scale (VAS) pain scale were obtained. Where the implementation of the research was carried out 8 times by giving Infra Red with a time of 15 minutes and the distance between the skin and Infra Red is 35-45 cm. Giving Infra Red provides the physiological effects needed in the patient's healing process, especially in patients with Low Back Pain Myogenic.Conclusion: It can be concluded that infra red has an effect in reducing pain in low back pain myogenic patients at the Hasta Husada Surgical Hospital.